Kashmir : a national plan to combat terrorism and insurgency - Kaajal Wallia (2008)
This thesis assesses and analyzes the Indian counterinsurgency campaign in Jammu and Kashmir. It essentially examines the Indian response in four elements that are considered vital in a winning counterinsurgency strategy: a) Unified command and coordination structure, b) Effective anti-terrorist legislations combined with confidence-building measures, c) Coordination within and between intelligence agencies, and, d) Foreign collaboration.